A LOOK AT ELIZABETH GILBERT’S REPERTOIRE IN EAT, PRAY, LOVE: AN ANALYSIS OF WOLFGANG ISER’S AESTHETIC RESPONSE - Kusumayanthi, Susie; Sayuti, Suminto A; Suryaman, Maman; Margana; Widyantoro, Agus (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2023)
This study aims to explore Elizabeth Gilbert's repertoire on the island of Bali in the novel Eat, Pray, Love and to reveal what Elizabeth Gilbert wants to convey through the novel. Eat, Pray, Love tells the story of Gilbert's journey in seeking inner peace in three countries, namely Italy, India, and Indonesia where each country gives her a different aspect of life. This research focuses on Elizabeth Gilbert's repertoire on her trip to the island of Bali in terms of Wolfgang Iser's Aesthetic Response theory. The data source of this research is a novel by Elizabeth Gilbert which was published in 2006 by Viking Penguin, USA. This research was conducted by tracing the reality of terrorism that had occurred in America in 2001 and in Bali in 2002 as the background. The data collection technique was carried out by reading notes accompanied by a careful and thorough recording of the entire novel related to Elizabeth Gilbert's repertoire. This research technique is carried out through the following steps: reading, identification, classification, interpretation, and inference. The results of this study are not directed at static and absolute meanings, but meanings that continue to move according to the expectations of each reader. Thus, science will continue to roll as the process of reading each at different times and socio-cultural realities.